The Influence of brand image, brand trust, and brand experience on brand loyalty - Nesi, Marsita; Yasri, Yasri (Universitas Negeri Padang, 2024)
This study aims to evaluate the impact of brand image, brand trust, and brand experience on brand loyalty among consumers in Padang City. The research employs a quantitative approach. The study population includes residents of Padang City aged 18 to 35 years who have used Avoskin products. A sample of 200 respondents was selected through a survey distributed via Google Forms. The data analysis technique used is Structural Equation Modeling (SEM) with Partial Least Squares (PLS), utilizing Smart PLS software. The findings indicate that: (1) brand image has a positive and significant effect on brand loyalty in Padang City; (2) brand trust exerts a positive and significant influence on brand loyalty in Padang City; (3) brand experience also has a positive and significant impact on Avoskin's brand loyalty in Padang City.